Transcriptional state and function of CD8 + memory T cells is linked to past proliferation (Nature immunology, 2022)
A new genetic ‘recorder’ of long-term cell proliferation revealed substantial heterogeneity in the division history of central memory CD8+ T cells. Importantly, the extent of past proliferation was related to distinct transcriptional features and re-expansion potential, highlighting an unappreciated division of labor within the central memory T cell pool.